Sex-Specific Development in Haplodiploid Honeybee Is Controlled by the Female-Embryo-Specific Activation of Thousands of Intronic LncRNAs - Wang, Miao; Chen, Dong; Zheng, Huoqing; Zhao, Liuwei; Xue, Xiaofeng; Yu, Fengyun; Zhang, Yu; Cheng, Chao; Niu, Qingsheng; Wang, Shuai; Zhang, Yi; Wu, Liming (Frontiers in Cell and Developmental Biology, 2021)
Embryonic development depends on a highly coordinated shift in transcription programs known as the maternal-to-zygotic transition (MZT). It remains unclear how haploid and diploid embryo coordinate their genomic activation and embryonic development during MZT in haplodiploid animals. Here, we applied a single-embryo RNA-seq approach to characterize the embryonic transcriptome dynamics in haploid males vs. diploid females of the haplodiploid insect honeybee (Apis mellifera). We observed typical zygotic genome activation (ZGA) occurred in three major waves specifically in female honeybee embryos; haploid genome activation was much weaker and occurred later. Strikingly, we also observed three waves of transcriptional activation for thousands of long noncoding transcripts (lncRNA), 73% of which are transcribed from intronic regions and 65% were specific to female honeybee embryos. These findings support a model in which introns encode thousands of lncRNAs that are expressed in a diploid-embryo-specific and ZGA-triggered manner that may have potential functions to regulate gene expression during early embryonic development in the haplodiploid insect honeybee.